2017
DOI: 10.1192/pb.bp.116.053967
|View full text |Cite
|
Sign up to set email alerts
|

Flexible assertive community treatment (FACT) model in specialist psychosis teams: An evaluation

Abstract: Aims and method The impact of flexible assertive community treatment (FACT) has been observed in people previously supported by assertive community treatment (ACT) teams, but its effect on those previously with a community mental health team (CMHT) has not been studied in the UK. An observational study was conducted of 380 people from 3 CMHTs and 95 people from an ACT team, all with a history of psychosis, following service reconfiguration to 3 FACT teams.Results People previously with a CMHT required less tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…To date, the effects of FACT have not been studied in the context of an RCT. Uncontrolled studies have shown a pre-post effect on symptoms and admissions [ 10 , 39 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…To date, the effects of FACT have not been studied in the context of an RCT. Uncontrolled studies have shown a pre-post effect on symptoms and admissions [ 10 , 39 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, despite the enthusiasm of service providers, the evidence base for the effectiveness of the adult Flexible ACT model remains sparse 24–26. Preliminary results have shown increased symptomatic remission of psychotic symptoms in patients with severe mental illness compared with controls receiving standard treatment,27 higher levels of psychosocial functioning,28 fewer hospital admissions and reduction of inpatient bed use,23 29 and increased compliance with treatment, decrease in unmet needs and improved quality of life 30. Flexible ACT has been shown to be more cost-effective compared with assertive outreach teams in England due to reductions in bed use, face-to-face contacts and changes in staffing 23.…”
Section: Introductionmentioning
confidence: 99%
“…However, the past few years have seen the closure of the majority of AO services in the United Kingdom, which was driven by the current economic climate and the negative findings of the only U.K. randomized controlled trial, which showed that care from AO teams did not reduce hospital admissions or improve clinical or social outcomes. While a number of observational studies have shown that alternative, less specialist, services were generally as effective as AO teams in reducing hospitalization none have specifically examined mortality in this patient group.…”
mentioning
confidence: 99%
“…While a number of observational studies have shown that alternative, less specialist, services were generally as effective as AO teams in reducing hospitalization[5][6][7] none have specifically examined mortality in this patient group.AO service in the English county of Northamptonshire (mixed urban and rural population of nearly 700,000 people, mainly White British; 85.7%) was disbanded in 2014. Three years later we followed up the cohort of 190 patients who were under the care of the AO service at the time of its closure.…”
mentioning
confidence: 99%